Dietary Diversity and Its Associated Determinants Among Senegalese Adolescent Girls - Nafissatou Ba Lo; Jérémie B. Dupuis; Aminata Ndene Ndiaye; El Hadji Momar Thiam; Aminata Diop Ndoye; Mohamadou Sall; Sonia Blaney (Adolescents)
Adolescence is a critical period for growth and development, yet research on dietary quality and its influencing factors among Senegalese adolescent girls is limited. This study aims to assess dietary quality, with a focus on dietary diversity (DD), and identify its determinants in a nationally representative sample of adolescent girls in Senegal. A cross-sectional study was conducted in 2023 among 600 girls aged 10–19 years. Food intake was assessed over a seven-day period to evaluate DD. Household food security and sociodemographic data were gathered through face-to-face interviews. Half the sample had adequate DD. As for consumption, 80% had breakfast daily, while the same proportion consumed one snack per day. Fruits and vegetables, meat/poultry/fish, and dairy were consumed daily by less than 25% of the sample. Sweet foods, sweet beverages, and salty and fried food were consumed by less than 10% every day. Not having been sick in the past two weeks (Odds ratio (OR): 1.53, Confidence Interval (CI): 1.05–2.22), taking breakfast daily (OR: 1.89, CI: 1.23–2.93) and micronutrients (OR: 2.75, CI: 1.54–4.92), listening to the radio at least once a week (OR: 1.66, CI: 1.05–2.63), and living in a household with access to an improved source of water (OR: 4.13, CI: 2.28–7.49) were positively associated with adequate DD. Overall, the diet of adolescent girls is of poor quality. Potential determinants of their dietary quality should be considered in future nutrition programs and policies to ensure their optimal growth and development.